Genome-Wide Identification and Expression Profiling of CONSTANS-Like Genes in Pepper (Capsicum annuum): Gaining an Insight to Their Phylogenetic Evolution and Stress-Specific Roles - Huang, Zhinan; Bai, Xueying; Duan, Weike; Chen, Boqing; Chen, Guodong; Xu, Binghua; Cheng, Rui; Wang, Jizhong (Frontiers in Plant Science, 2022)
COL (CONSTANS-like) genes play important regulatory roles in multiple growth and development processes of plants but have rarely been studied in Capsicum annuum. This study explored the evolutionary relationship and expression patterns of COL genes from C. annuum. A total of 10 COL genes were identified in the genome of the cultivated pepper Zunla-1 and were named CaCOL01-10. These genes were unequally distributed among five chromosomes and could be divided into three groups based on differences in gene structure characteristics. During evolutionary history, duplications and retentions were divergent among different groups of COL genes. Tandem duplication caused amplification of group I genes. Genetic distance among COL genes was the largest in group III, suggesting that group III genes undergo more relaxed selection pressure compared with the other groups. Expression patterns of CaCOLs in tissues were significantly different, with CaCOL08 exhibiting the highest expression in stem and leaf. Some COL orthologous genes showed markedly different expression patterns in pepper compared with tomato, such as COL_1 orthologs, which may be involved in fruit development in pepper. In addition, CaCOLs participated in the regulation of abiotic stresses to varying degrees. Five CaCOL genes were induced by cold, and CaCOL02 and CaCOL03 were specifically upregulated by cold and downregulated by heat. This study provides a theoretical basis for in-depth understanding of the functions of COL genes in pepper and their molecular mechanisms involved in growth and development and responses to abiotic stresses.